Characteristics of the batokine exchange dynamics in patients with coronary heart disease and obesity on the background of therapy - Gridneva, Olga (My University, 2023)
Вивчено батокиновий обмін у хворих на ішемічну хворобу серця та ожиріння.
Keywords: coronary heart disease; obesity; 2023а